Evaluating zoonotic metacestodes: gross and histopathological alterations of beef in north–west Ethiopia one health approach for meat inspection and animal management - Alene, Dessie; Maru, Moges; Demessie, Yitayew; Mulaw, Asnakew (Frontiers in Veterinary Science, 2024)
Zoonotic metacestodes present a significant threat to both veterinary and public health. Specifically, the prevalence of metacestodes is often concentrated among consumers of raw meat and underdeveloped countries. The objective of this study was to estimate the prevalence of condemned red offal and examine the gross and histopathology features of zoonotic metacestodes. A crosssectional study was conducted from November 2022 to July 2023 at the Bahir Dar municipal abattoir. A simple random sampling method employed in the abattoir survey to investigate pathological changes of offal and its rate of condemnation. Following a gross inspection of the red offal, representative tissue samples collected and preserved in 10% neutral buffered formalin.Subsequently, the size and number of cysts determined, and their viability and fertility evaluated.Hematoxylin and eosin staining utilized to analyze various lesions with microscope. A total of 340 cattle examined and 7.5 % red offal condemned due to hydatid cysts 4.12% in the lungs, 3% in the liver, 0.6% in the kidneys, and 0.9% in other organs. Red offal condemned due to Cysticercus bovis 0.6% in the liver and 0.3% in the tongue. A statistically significance relationship was found between lung rejection due to hydatidosis (P<0.05), body condition score, and origin of the animal. Among the detected calcified cysts, 83.34% of Cysticercus bovis and 47.62% of hydatid cysts.Histopathological examination revealed hydatid cysts and their oncospheres within the portal circulation, as well as necrotized, calcified daughter cysts observed on Bowman's capsule. The alveoli and bronchiole parenchyma compressed with pressure of protoscolices and it infiltrated by eosinophils. The cyst wall is attached to the thick hepatic capsule of the liver, with the hepatic parenchyma displaying islands of irregular hepatocytes. Cysticercus bovis detected in the deteriorated and necrotized muscle bundles, along with granulomatous lesions characterized by infiltration of mononuclear cells. Gross and histological examinations is invaluable tool for diagnosing hydatidosis and cysticercosis, providing well-organized baseline data to enhance our understanding the burden of zoonotic metacestodes.